Analisis Implementasi Kebijakan Program Penanggulangan Stunting Terintegrasi Di Kabupaten Lombok Utara - Hermawati, Hermawati; Sastrawan, Sastrawan (Universitas Qamarul Huda Badaruddin, 2020)
Interventions for reducing stunting with various programs at the administrative level are very weak, so it is necessary to describe an analysis of the implementation of policies for the integrated stunting reduction program in Kabupaten Lombok Utara in 2020. The method used in this research is descriptive qualitative research, while the data sources in this study are the Health Office, Regional Secretariat, Regional Development Planning Agency, Population Control Office, Family Planning, Community and Village Empowerment (DP2KBPMD) North Lombok Regency. Furthermore, the purpose of this research is how to implement an integrated stunting prevention program policy in North Lombok Regency. Based on the results of the analysis and discussion above, it can be concluded that the integrated stunting management program has not been fully implemented due to the many technical problems that occurred during the implementation of program activities in each OPD in the field.